PENGARUH LIKUIDITAS, SOLVABILITAS, PROFITABILITAS TERHADAP NILAI PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA - Neti Erlina (Jurnal Manajemen Kompeten, 2018)
Effect of liquidity, solvency, profitability against mining company value in indonesian stock exchange (BEI).purpose to determine the effect of liquidity, solvency, profitability of the value mining company in indonesian stock exchange (BEI). the data used in this research is the data time series,a variabel which is used liquidity Current Ratio, Cash Ratio, Solvency Debt To Equity Ratio, Debt To Aset Ratio, profitability Net Profit Margin, Earning Pershare again the study population valueof the company is amining company listed on the indonesian stock exchange period 2009-2013. The technique of taking sample uses purposive sampling and obtained 14companies were selected as sample.the analysis technique used in this researchis to test assumtions of linear regression. including normality test heterokedastisitas test, multicolinearity test, autocorrelation test, test the hypothesis that the F test and t test.fidding indicates that the variable liquidity (Current Rasio X1,Cash Rasio X2), solvency (Debt To Asset Ratio X3, Debt To Equity Ratio X4), profitability Net Profit Margin (X5),Earning Pershare (X6) on mining company indonesian stock exchange shows influence significant together against the value of company.partial Current Rasio (X1),Cash Rasio (X2), Debt To Asset Ratio (X3), Debt To Equity Ratio (X4), Net Profit Margin (X5),Earning Pershare (X6)had no significant effect on firm value.